THE INFLUNCES OF USING PICTURES SERIES IN STUDENT’S WRITING COMPOSITION TO THE EIGHTH GRADE STUDENTS OF SMP PGRI 1 PALEMBANG - Etty Pratiwi (Jurnal Dosen Universitas PGRI Palembang, 2016)
Abstract: this research investigated the influence of using pictures series in student’s writing composition  to the eighth grade students of SMP PGRI 1 Palembang. The objective of this study was to identify whether or not by using pictures series can improve the students ‘ writing composition. This study was conducted in experimental research to 82 students from the eighth grade students of SMP PGRI 1 Palembang of the academic year of 2016-2017. This study could be concluded that pictures series strategy gave a significant improvement for the students’ writing composition than the students’ writing composition by using conventional strategy to the eighth grade students of SMP PGRI 1 Palembang. Key Words:  Pictures stories, Writing Composition